Minutes of the CCAFS 9th Independent Steering Committee Meeting, 25 May & 01 June 2021 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In May and June 2021 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its 9th virtual Independent Steering Committee meeting.